300 GHz InP HBT amplifier with 10 mW output power. Issue 5 (1st February 2014) - Yu, H.G.; Choi, S.H.; Jeon, S.; Kim, M.
Abstract : A high‐power terahertz solid‐state amplifier fabricated using 0.25 μm InP heterojunction bipolar transistor (HBT) technology is reported. This amplifier utilies a novel defective‐ground four‐way balun to combine differential amplifier chains for a total output device periphery of 40 μm. A significant amount of power of ∼10 mW is obtained at 305 GHz with better than 20 dB small‐signal gain.